Intracytoplasmic Sperm Injection May Not Improve Clinical Outcomes Despite Its Positive Effect on Embryo Results: A Retrospective Analysis of 1130 Half-ICSI Treatments - Peng, Nan; Ma, Shuiying; Li, Cheng; Liu, Hui; Zhao, Haibin; Li, Lian-Jie; Li, Qing; Li, Mei (Frontiers in Endocrinology, 2022)
Objective: To explore the clinical application value of half-ICSI treatment for infertility in assisted reproductive technology. Method: A retrospective analysis of 1130 half-ICSI treatments was conducted at the Affiliated Reproductive Hospital of Shandong University from January 2011 to December 2015. Patients with low fertilization rates in previous cycles, primary infertility for >5 years with unexplained reason, or secondary infertility for >5 years without fallopian tube factor were involved in this study. The 2PN rate, high-quality embryo rate, oocyte utilization rate, and clinical outcomes were compared between IVF insemination group (IVF group) and ICSI insemination group (ICSI group). The clinical outcome of half-ICSI insemination treatment, grouped according primary and secondary infertility, was also analyzed. Results: Compared with IVF, ICSI resulted in a significantly higher 2PN rate (74.8% vs. 62.9%), high-quality embryo rate (54.6% vs. 51.7%), and oocyte utilization rate (35.9% vs. 32.8%; P<0.05). Among the 885 fresh-embryo transfer cycles, there were no notable differences in clinical pregnancy rate, live birth rate, or neonatal abnormality rate between the IVF and ICSI groups. Among the 792 primary infertility cycles, ICSI resulted in a significantly higher 2PN rate, high-quality embryo rate, and oocyte utilization rate compared with IVF (75.3% vs. 62.4%, 54.3% vs. 50.8%, 36.4% vs. 32.6%, P<0.05). For the 338 secondary infertility cycles, ICSI resulted in a significantly higher 2PN rate (73.6% vs. 63.9%, P<0.05) compared with IVF, but there were no notable differences in other laboratory results. Moreover, the biochemical pregnancy rate of the ICSI group was significantly lower than for IVF in secondary infertility cycles (49.3% vs. 65.6%; P<0.05). A total of 89 cycles (7.9%) with complete IVF fertilization failure showed a low second polar body (2PB) rate (33.6%) after a 5-h short-time fertilization period, including 34 cycles (3.0%) with no 2PB oocytes observed in the IVF group. Conclusion: ICSI insemination improved laboratory results compared with IVF insemination, however, fresh-embryo transfer of ICSI originated embryos did not improve clinical pregnancy and live birth rates. Rescue ICSI has been successfully applied in clinical IVF insemination to avoid fertilization failure. Therefore, as an extra intervention, it is suggested that ICSI be used judiciously.